BIOPIGMENT EXPRESSION OF MICROALGAE Chlorella sp. AND ITS APPLICATION FOR AS A SENSITIZER OF SOLAR CELLS - Kurnia, Dewi
As known, microalgae can be used as an alternative energy feedstock of biodiesel and bioethanol. Additionally, microalgae also produce biopigments that can be used as a sensitizer for solar cells. Natural dyes that have been tested as sensitizes are chlorophylls, carotenoids, and anthocyanins obtained from fruits and vegetables. In the present study, the expression of photosynthetic pigments from tropical marine microalgae Chlorella sp. and its application for the solar cell sensitezer were investigated. Chlorella sp. biomass was produced in two different media: Walne medium and GM10 modified medium. Crude extract pigment was obtained from the extraction of dried biomass in acetone (1:8 w/v) for five cycles. Purified pigments obtained from the purification using silica column chromatography with acetone:hexane (3:7 v/v) as eluent. The results showed that the concentrations of chlorophyll a, chlorophyll b, and total carotenoids obtained from biomass cultured in Walne medium were 1,418 ± 71, 533 ± 36, and 434 ± 19, respectively, while in GM10 modified medium were 928 ± 61, 352 ± 23, and 337 ± 23, respectively. The analysis of variance test (P < 0,05) for the production of pigments in two different media showed Fcalc > Fcrit indicating significant difference on the expression of pigments produced in Walne medium compared with those in GM10modified medium. Seven photosynthetic pigments were successfully identified by UV-Vis spectrophotometer. They were ?-carotene (452 and 477 nm), pheophytin a (420 and 665 nm), chlorophyll a (430 and 662 nm), chlorophyll b (452 and 646 nm), lutein-5,6-epoxide (420,440 and 470 nm), ?- zeacarotene (398, 421 and 449 nm), and violaxanthin (415, 437 and 466 nm). The characteristics of photovoltaic cells of ?-carotene sensitized solar cells were Jsc of 0.0051 mA/cm2, Voc of 0.056 V, Jmpp of 0.0027 mA/cm2, Vmpp of 0.03 V, fill factor value of 0.25, and efficiency of 7.3 × 10–5%. Whereas, solar cells sensitized by a mixture of ?-carotene and chlorophyll a in a molar concentration ratio of 1:6 showed values Jsc of 0.0063 mA/cm2, Voc of 0.043 V, Jmpp of 0.0035 mA/cm2, Vmpp of 0.02 V, fill factor value of 0.29, and efficiency of 7.46 × 10–5%. These results suggest that ?-carotene and chlorophyll a from microalgae Chlorella sp. can be used as a sensitizer for solar cells.